2007
DOI: 10.1111/j.1567-1364.2006.00183.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity ofDekkera bruxellensisyeasts isolated from Australian wineries

Abstract: Yeasts of the genus Dekkera and its anamorph Brettanomyces represent a significant spoilage issue for the global wine industry. Despite this, there is limited knowledge of genetic diversity and strain distribution within wine and winery-related environments. In this study, amplified fragment length polymorphism (AFLP) analysis was conducted on 244 Dekkera bruxellensis isolates from red wine made in 31 winemaking regions of Australia. The results indicated there were eight genotypes among the isolates, and thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
72
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(77 citation statements)
references
References 49 publications
5
72
0
Order By: Relevance
“…1.85 (SoftGenetics LLC, Pennsylvania). An automatic panel editor for scoring was used for each selective primer combination (Curtin et al 2007), including alleles of 150-510 base pairs, and then modified manually. The repeatability of the AFLP fragments was tested as the ratio of number of fragment differences/total number of comparisons (Bonin et al 2004) using replication of ten percent of the total individuals.…”
Section: Methodsmentioning
confidence: 99%
“…1.85 (SoftGenetics LLC, Pennsylvania). An automatic panel editor for scoring was used for each selective primer combination (Curtin et al 2007), including alleles of 150-510 base pairs, and then modified manually. The repeatability of the AFLP fragments was tested as the ratio of number of fragment differences/total number of comparisons (Bonin et al 2004) using replication of ten percent of the total individuals.…”
Section: Methodsmentioning
confidence: 99%
“…However, the genotype of the isolates was not further studied. In a recent publication 8 it was reported that 244 isolates from 31 winemaking regions in Australia, resulted in 8 genotypes being found, suggesting common points of origin of some strains.…”
Section: Behaviour During Fermentationmentioning
confidence: 99%
“…Little is available in the literature regarding these points. Two studies have compared isolates from different wine regions, but not from the same cellars 7,8 . Our study thus consisted of screening B. bruxellensis strains isolated from wines coming from two cellars in order to determine if they had similar or different characteristics, and focusing on their behaviour during fermentation using a synthetic wine medium.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the species is of increasing relevance for the biofuel industry (8). Apart from isolations from beer and wine, Brettanomyces species have been detected and isolated in other foods, such as cider, soft drinks, dairy products, and olives (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Despite its economic importance either as a spoilage contaminant in wine and nonalcoholic beverages or as a vital component of the fermentation biota in the production of certain beers, the physiology and ecology of Brettanomyces yeasts have only recently been the subject of intensive research (1,(21)(22)(23)(24)(25).…”
mentioning
confidence: 99%